Estimation of glomerular filtration rate from plasma creatinine concentration in children. Issue 11 (November 1976) - Counahan, R; Chantler, C; Ghazali, S; Kirkwood, B; Rose, F; Barratt, T M
Abstract : The relation between the true plasma creatinine concentration (Pc) and the glomerular filtration rate corrected for body surface area (GFR/SA) was investigated in 108 individuals, and the following formula was derived: GFR/SA (ml/min per 1-73m2SA) = 0-43 Ht (cm)/Pc (mg/100 ml). This formula was tested in a second group of 83 children, and its accuracy and precision was compared to the 24-hour creatinine clearance. It was found to be superior to the creatinine clearance overall, and was as good, even if all results involving suspect 24-hour-urine collections were eliminated from analysis. The formula in SI usage is: GFR/SA (ml/min per 1-73 m2SA) = 38 Ht (cm)1Pc (mumol/l).